2007
DOI: 10.1021/ac7016579
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Resolved Gene Technology for Multiplexed Bioluminescence and High-Content Screening

Abstract: The availability of new bioluminescent proteins, obtained by cDNA cloning and mutagenesis of wild-type genes, expanded the applicability of these reporters from the perspective of using more proteins emitting at different wavelengths in the same cell-based assay. By spectrally resolving the light emitted by different reporter proteins, it is in fact possible to simultaneously monitor multiple targets. A new luciferase isolated from Luciola italica has been recently cloned, and thermostable red- and green-emitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Many luciferases which are expressed intracellularly and emit different colored light (green and red-emitting luciferases from click beetle (Caysa et al, 2009; Takeuchi et al, 2010) and the American or Italian firefly (Branchini et al, 2007)) have been cloned. Secreted variants of these lucifrases could be engineered and multiplexed with Gluc for multicolor applications using spectral unmixing (Gammon et al, 2006; Michelini et al, 2008). …”
Section: Trends In Development Of Novel Secreted Reportersmentioning
confidence: 99%
“…Many luciferases which are expressed intracellularly and emit different colored light (green and red-emitting luciferases from click beetle (Caysa et al, 2009; Takeuchi et al, 2010) and the American or Italian firefly (Branchini et al, 2007)) have been cloned. Secreted variants of these lucifrases could be engineered and multiplexed with Gluc for multicolor applications using spectral unmixing (Gammon et al, 2006; Michelini et al, 2008). …”
Section: Trends In Development Of Novel Secreted Reportersmentioning
confidence: 99%
“…Other BRET studies involving various GPCR hetero-dimerization has suggested that Renilla luciferase and EYFP as energy transfer partners is limited as the emission spectrum from the luciferase tends to obscure the energy transfer output from EYFP [47]. Using the same RLuc-EYFP BRET format, HTS assays were developed for evaluation of the estrogen-like and androgen-like activity from biological and environmental samples [48][49][50]. The "in vivo" BRET quantitative assay was then developed by coexpressing the two fusion proteins in mammalian cells.…”
Section: High-throughput Screeningmentioning
confidence: 99%
“…Indeed, Nishide et al performed circadian transcription analysis using FLuc and Vargulla luciferase for cultured tissues from transgenic animals [45], and Michelini et al demonstrated a triple reporter gene assay system that was developed in the high-throughput 96-well micro titer plate format combining two different intracellular FLuc variants as reporters and a secretory luciferase as internal control [46,47].…”
Section: Secretory Luciferasementioning
confidence: 99%